Pengaruh Efektivitas Penanganan Pengaduan terhadap kepuasan Masyarakat di Dinas Kependudukan dan Pencatatan Sipil Kota Semarang - Indira Setia Ningtyas (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
The Ombudsman's annual report shows the local government as the most often agency which gets complaints because it is the closest layer to the public. The Department of Population and Civil Registry of the City of Semarang as one of the agencies that received the highest complaint report held a complaint that serves as a follow-up to the complaints problem as well as to improve public services. This study aims to know how the effectiveness of complaints handling on community satisfaction in the Department of Population and Civil Registry of Semarang City. The study used is the principles by Gorton, namely from improving quality, openness, commitment, accessibility, ability to react, transparency and responsibility, as well as privacy and confidentiality. The method used a sequential explanatory by taking sample of 111 people to answer the questionnaire. Besides that, used data collection techniques through interviews, documentation, and observation. The results of the effectiveness variable handling complaints of 79.17 can be categorized as effective in dealing with public complaints and community satisfaction of 39.43 assessed in the satisfactory category. The results of the study the effect of the effectiveness of handling complaints against community satisfaction by 71.4%. So the results of the significance test show that the initial hypothesis which shows